Adaptive Online Exam System - Sawayafa, Khalil; Abu Maizar, Abdulrazzaq (جامعة بوليتكنك فلسطين - تكنولوجيا المعلومات, 2012)
Technology has a great impact in the use of educational process. Testing is an important aspect of the educational process that aims to the evaluation and getting feedback of the improvements and changes in the ability of the students' minds. Furthermore, facing the same type of fixed exams that treats all students the same ignoring the level of knowledge they have is always affecting the students' evaluation and also is a supportive factor of their bad behavior of cheating. To use technology to help students in the testing process the adaptive exam evolution was adapted as to give every student a relative exam according to his/her level of knowledge. The main idea of the functionality of the adaptive exam system is the . . estimation of the examinees ability after the answer of every question and proceeds with giving an appropriate level of question until the termination condition of the exam is achieved.
no of pages 84, 25375, تكنولوجيا المعلومات 3/2012 , in the store
Keywords: Exam Systems Online